Kualitas Estrus pada Domba Garut Setelah Sinkronisasi Estrus Menggunakan Prostaglandin, Progesterone dan Kombinasinya - Cristóvão, Adelaide José Pereira; Setiadi, Mohamad Agus; Setiadi, Dedi Rahmat; Mohamad Agus Setiadi (Acta VETERINARIA Indonesiana, 2025)
Estrus synchronization is a technique used to stimulate estrus and ovulation in a group of animals using hormones. This study aimed to compare three estrus synchronization methods. Fifteen female garut sheep were used and treated with: progesterone-CIDR, double injection prostaglandins, and their combination. At standing heat, ewes were mated with a buck. The parameters measured include the onset estrus, duration estrus, pattern of electrical impedance in the vaginal mucus, number and size of follicles, and pregnancy status. All treated ewes responded to estrus (100%). There were different onset of estrus, namely CIDR (54h), CIDR+PGF2α (41h), and double injection of PGF2α (49.4h), respectively. Meanwhile, the Duration of estrus of CIDR (30,6h), CIDR+PGF2α (29.8h), and double injection of PGF2α (22.4h), respectively. Furthermore, electrical impedance of vaginal mucus at standing heat were CIDR (208Ω), CIDR+PGF2α (189Ω) and double injection of PGF2α (305Ω). The follicle size on H0 to standing heat in each group was significant (p<0.05), while the follicle count was significant only (p<0.05) in the CIDR group. Pregnancy rate was achieved by synchronization with CIDR and double injection prostaglandin (100%) compared to CIDR+PGF2α (40%). It's concluded that the third method of synchronization could result in the best estrus response with slight different characteristics.